Pemberdayaan Masyarakat Desa Sucopangepok Kabupaten Jember Melalui Pengembangan dan Pemasaran Produk Sedotan Bambu - Kuswardhani, Nita; Haidar Ali; Yumni, Syafiya Zata; Rahayu, Supratiana; Nugraha, Bima Arya; Larasati R, Khosyi; Faqih A, Abdillah; Khumairoh, Luthfi Afrilia; Mahendra, Enggar Lantang (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The “Hibah Mahasiswa Berdesa” Program (Promahadesa) is conducted in Sucopangepok Village, Jelbuk District, Jember Regency, which has potential of bamboo. Based on observation results, the use of bamboo as a potential for maked bamboo straws hasn't been utilized optimally. There is a main problem, that is the ability to market products and expand information is limited. In addition, the marketing area for bamboo straws isn't wide enough. Through the “Hibah Mahasiswa Berdesa” program (Promahadesa) will be assisted in optimize the  marketing of bamboo straws and improve the marketing system.  This activity realized use of technology web communication and digital marketing to improve product visualization. The implementation stage with socialization regard the application of digital marketing, marketplace to the practice of its use. The expected results after the training indicate an expanded  customer accept of bamboo straws.  So, optimal development and marketing of bamboo straws can improve the community’s economy